Ergosterol purification from basidiomes of Clouded Agaric (Clitocybe nebularis (Fr.) Kumm.) - V. O. Antonyuk (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
Ergosterol (ergosta-5 ,7,22-trien-3β-ol ) is a compound found only in fungi. Ergosterol has medical interest, as it is easily converted into Vitamin D2. In the previous work we have studied 22 species of true fungi. The highest quantity of ergosterol was found in basidiomes of Clouded Agaric (Clitocybe nebularis (Fr.) Kumm). Meanwhile, there is no data on the purification of ergosterol from this fungus in the literature.